(untitled) (Plant Tissue Culture and Biotechnology, 2016)
Cotyledon explants of sweetgourd (Cucurbita moschata Duch.) were cultured on MS supplemented with different concentrations of BAP alone and in combination with NAA, TDZ and 2,4?D. High shooting frequency (94.4%) was obtained from BARI Mistikumra?1 when cotyledon segments were cultured on MS with 4.44 ?M BAP alone. The highest number (8.9) of shoot development and minimum days (14.7) required for shoot induction were also observed in 4.44 ?M BAP treatment for BARI Mistikumra?1. In contrast, 83.3% shooting frequency were observed from BARI Mistikumra?2 producing 11.9 shoots in 8.4 days on 8.88 ?M BAP. The regenerated shoots of both varieties were rooted on half strength of MS and MS supplemented with 0.53 ?M NAA and 2.46 ?M IBA. Rooting was observed in BARI Mistikumra?1 with 92.6% frequency in 12.3 days whereas it took 8.6 days with 93.3% rooting frequency in BARI Mistikumra?2 when shoots were cultured on MS supplemented with 0.53 ?M NAA. Welldeveloped rooted plantlets were transferred to pots containing sterile soil and covered with polythene bags in the greenhouse for hardening. The acclimated plants were planted in the field after three weeks. Plant Tissue Cult. & Biotech. 26(1): 67-75, 2016 (June)